Ethnobotanical knowledge of Bantar community in Shambhunath Rural Municipality of Saptari District, Nepal (Rajarshi Janak University Research Journal, 2025)
The study has been carried out to document the ethnobotanical knowledge of the Bantarommunity in the Shambhunath Rural Municipality of the Saptari district, Nepal. This study explores the traditional utilization of plant resources by the Bantar people for medicinal, nutritional, and ritualistic purposes. A combination of field surveys, semi-structured interviews, and participatory observation was conducted to document the community's practices. A total of 50 plant species belonging to 33 families and 48 genera, comprising 24 herbs, 14 trees, 6 shrubs, and 6 climbers, were identified as integral to their ethnobotanical repertoire. Most of these plants were used for treating ailments such as fever, gastrointestinal disorders, respiratory issues, and skin diseases, while some plants were used for nutrition and also for cultural ritual purposes. The findings reveal a sustainable relationship between the community and their local environment, reflecting a holistic approach to health and well-being. However, modernization and declining intergenerational knowledge transfer pose significant threats to preserving this traditional wisdom. The study underscores the need for immediate documentation and integration of ethnobotanical knowledge into broader conservation and public health strategies. Protecting such cultural heritage is essential for biodiversity conservation and fostering sustainable use of these plants in the region. By highlighting the Bantar community's ethnobotanical practices, this research contributes to understanding Nepal's rich bio-cultural diversity.